PENGARUH EFIKASI DIRI, MINAT BELAJAR, FASILITAS BELAJAR, TEMAN SEBAYA DAN PERAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA PELAJARAN EKONOMI - Melan Dwi Sagita; Amelia, Mona; Nisha Selvia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of self-efficacy, learning interest, learning facilities, peers, and parental roles on the academic achievement of 11th grade students in Economics subjects at SMA Negeri 1 Basa Ampek Balai. This research employed a quantitative approach with a survey method. The population comprised 130 students, and samples were determined using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results revealed that self-efficacy, learning facilities, peers, and parental roles significantly influence learning achievement, whereas learning interest has no significant effect. Simultaneously, all independent variables significantly affect student achievement. These findings emphasize the importance of both internal and external factors in supporting students' academic outcomes. Therefore, collaboration among students, teachers, schools, and parents is essential to improve learning quality.